2020
DOI: 10.1007/s12080-020-00464-9
|View full text |Cite
|
Sign up to set email alerts
|

Local control of resource allocation is sufficient to model optimal dynamics in syntrophic systems

Abstract: Syntrophic systems are common in nature and include forms of obligate mutualisms in which each participating organism or component of an organism obtains from the other an essential nutrient or metabolic product that it cannot provide for itself. Models of how these complementary resources are allocated between partners often assume optimal behavior, but whether mechanisms enabling global control exist in syntrophic systems, and what form they might take, is unknown. Recognizing that growth of plant organs tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…Throughout the growing season, fractions of carbon u SC (t), u RC (t), and u F C (t) and fractions of nitrogen u SN (t), u RN (t), and u F N (t) are allocated to the shoots, roots, and fruits, respectively, at time t. The resources pass through a synthesizing unit (SU) in each organ, where they are converted into biomass. We use Kooijman's parallel complementary synthesizing unit (PCSU) function from Kooijman (2010), employing the same simplification seen in (Ledder et al 2020, Appendix A), given by g(A, B) =…”
Section: Model Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the growing season, fractions of carbon u SC (t), u RC (t), and u F C (t) and fractions of nitrogen u SN (t), u RN (t), and u F N (t) are allocated to the shoots, roots, and fruits, respectively, at time t. The resources pass through a synthesizing unit (SU) in each organ, where they are converted into biomass. We use Kooijman's parallel complementary synthesizing unit (PCSU) function from Kooijman (2010), employing the same simplification seen in (Ledder et al 2020, Appendix A), given by g(A, B) =…”
Section: Model Setupmentioning
confidence: 99%
“…It has also been suggested that allocation may be an emergent property of the many processes involved in plant growth rather than the result of a central allocation process (Feller et al 2015). For a more complete review of allocation theory, we refer the reader to Ledder et al (2020) or Poorter et al (2012).…”
Section: Introductionmentioning
confidence: 99%
“…The conceptual foundation within DEB theory for such models is the work by Kooijman ( 2001 ), which sketches links involving excretion fluxes from animal host and algal symbiont in corals and interactions between root and shoot in a plant. Subsequent models for the coral symbiosis and the interaction of roots and shoots in plants have been developed in Muller et al ( 2009 ), Cunning et al ( 2017 ), Ledder et al ( 2020 ) and Schouten et al ( 2020 ). These models can be applied to describe responses to environmental stress, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematically, several of the cited models take the form of differential equations that involve a small number of state variables. For instance, the models in ( Cunning et al , 2017 ) and Ledder et al ( 2020 ) describe two ‘players’ who exchange metabolic products that are surplus to their own needs. This interaction is described with a set of algebraic equations that characterize the flows of elemental matter within an interaction network; see schematic Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation